2017
DOI: 10.1038/leu.2017.350
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of pre-leukemic clones during first remission and risk of relapse in acute myeloid leukemia

Abstract: Some patients with acute myeloid leukemia (AML) who are in complete remission after induction chemotherapy harbor persisting pre-leukemic clones, carrying a subset of leukemia-associated somatic mutations. There is conflicting evidence on the prognostic relevance of these clones for AML relapse. Here, we characterized paired pre-treatment and remission samples from 126 AML patients for mutations in 68 leukemia-associated genes. Fifty patients (40%) retained ≥1 mutation during remission at a variant allele freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…In fact, age-related clonal hematopoiesis (ARCH) is driven by mutations also commonly found in MDS and AML (e.g. especially in the genes DNMT3A, TET2, ASXL1, JAK2 , or TP53 ) [ 11 , 12 , 21 , 22 , 23 ]. The condition is associated with an increased risk to develop a myeloid malignancy including MDS, as well as with an increased all-cause mortality, especially by cardio-vascular events [ 11 , 12 ].…”
Section: The Molecular Landscape In Mdsmentioning
confidence: 99%
“…In fact, age-related clonal hematopoiesis (ARCH) is driven by mutations also commonly found in MDS and AML (e.g. especially in the genes DNMT3A, TET2, ASXL1, JAK2 , or TP53 ) [ 11 , 12 , 21 , 22 , 23 ]. The condition is associated with an increased risk to develop a myeloid malignancy including MDS, as well as with an increased all-cause mortality, especially by cardio-vascular events [ 11 , 12 ].…”
Section: The Molecular Landscape In Mdsmentioning
confidence: 99%
“…Moreover, AML relapse was characterized by the expansion of the FLT3 -ITD clone that was reduced but not eradicated by the treatment, with an increase of allelic ratio from 0.09 (diagnosis) to 0.21 (relapse). A recent study showed that the persistence of DNMT3A mutation at a VAF ≥2% at first remission is a common event in AML, occurring in 65% of cases with mutation at diagnosis and is associated with older age and inferior relapse-free survival [32].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the observed negative selection against cells with biallelic TET2 mutation in vivo, 5-Aza treatment rarely resulted in the complete elimination of TET2 null cells, consistent with data from the index patient in whom 5'-Aza-induced morphological remission was characterized by the persistence of cells with biallelic TET2 mutation. Mutation persistence in morphological remission has been reported for several leukemia driver genes, including those characteristic of age-associated clonal hematopoiesis such as TET2, DNMT3A, SRSF2, RUNX1 and ASXL1 [32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%